2014
DOI: 10.3389/fncel.2014.00433
|View full text |Cite
|
Sign up to set email alerts
|

GNX-4728, a novel small molecule drug inhibitor of mitochondrial permeability transition, is therapeutic in a mouse model of amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurological disorder in humans characterized by progressive degeneration of skeletal muscle and motor neurons in spinal cord, brainstem, and cerebral cortex causing skeletal muscle paralysis, respiratory insufficiency, and death. There are no cures or effective treatments for ALS. ALS can be inherited, but most cases are not associated with a family history of the disease. Mitochondria have been implicated in the pathogenesis but definitive proof of causal mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 45 publications
(74 reference statements)
3
61
0
Order By: Relevance
“…Thus, maintaining Ca 2+ homeostasis might be of therapeutic benefit in ALS. We have shown recently that increasing mitochondrial Ca 2+ retention capacity with a mitochondrial permeability transition pore inhibitor has remarkable therapeutic effects in ALS mice (Martin et al, 2014). Other studies showed that limiting Ca 2+ influx by manipulating glutamate receptors is protective in ALS mouse models (Tateno et al, 2004; Tortarolo et al, 2006; Van Damme et al, 2005; Van Damme et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, maintaining Ca 2+ homeostasis might be of therapeutic benefit in ALS. We have shown recently that increasing mitochondrial Ca 2+ retention capacity with a mitochondrial permeability transition pore inhibitor has remarkable therapeutic effects in ALS mice (Martin et al, 2014). Other studies showed that limiting Ca 2+ influx by manipulating glutamate receptors is protective in ALS mouse models (Tateno et al, 2004; Tortarolo et al, 2006; Van Damme et al, 2005; Van Damme et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a potent cinnamic anilide has been observed to inhibit mPTP opening in response to Ca 2+ overload, oxidative stress, and activation by chemical cross-linkers36. Interestingly, a variant cinnamic anilide was able to cross the blood-brain barrier giving potential utility in neurodegenerative disorders where dysfunctional mitochondria have been observed to play a role, such as amyotrophic lateral sclerosis (ALS)37. The cinnamic anilide, GNX-4728 slowed disease progression in a mouse model of ALS, producing a 2-fold increase in lifespan37.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a variant cinnamic anilide was able to cross the blood-brain barrier giving potential utility in neurodegenerative disorders where dysfunctional mitochondria have been observed to play a role, such as amyotrophic lateral sclerosis (ALS)37. The cinnamic anilide, GNX-4728 slowed disease progression in a mouse model of ALS, producing a 2-fold increase in lifespan37. Much like ER-000444793, a final class of compounds has been identified which inhibited mPT across species with no effect on ATP synthesis and mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, CypD deletion studies show benefit in mouse models of amyloid lateral sclerosis and Parkinson's diseases as genetic ablation of CypD delayed the onset of disease and extended lifespan (Martin, Semenkow, Hanaford, & Wong, 2014; Martin et al., 2009), strengthening the role of the mPTP in the mechanisms of both diseases. The beneficial effect observed with a novel small mPTP inhibitor in a mouse model of amyloid lateral sclerosis confirmed that the mPTP could represent an interesting target for drug development in amyloid lateral sclerosis (Martin, Fancelli, et al., 2014). This is in line with the data of Keep, Elmér, Fong, and Csiszar (2001) who observed an improvement by CsA of the motion disorders in an amyloid lateral sclerosis mouse model.…”
Section: Evidence For the Involvement Of Mptp Opening In Age‐associatmentioning
confidence: 99%